1988
DOI: 10.1159/000125036
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrinological Function in Alzheimer’s Disease

Abstract: The neuroendocrine function is regulated by several neurotransmitters (acetylcholine, dopamine, somatostatin and noradrenaline) known to be reduced in brains of patients with Alzheimer’s disease (AD). Moreover, the hypothalamus also has pathological changes. In spite of these findings suggesting neuroendocrine dysfunctions, this function has seldom been investigated in AD patients so far. We have compared patients with clinically ‘probable’ AD of mild-to-moderate severity with nondemented age- and sex-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
2
7
1
Order By: Relevance
“…In humans a decreased level of (3-endorphin ((3-End)-like-immunoreactivity in cerebrospinal fluid of patients with AD [ 123] and with ATD [124] has been described. This finding was not confirmed in more recent studies [108] and others found increased plasma levels in AD patients [125].…”
Section: ] /}-Endorphincontrasting
confidence: 65%
“…In humans a decreased level of (3-endorphin ((3-End)-like-immunoreactivity in cerebrospinal fluid of patients with AD [ 123] and with ATD [124] has been described. This finding was not confirmed in more recent studies [108] and others found increased plasma levels in AD patients [125].…”
Section: ] /}-Endorphincontrasting
confidence: 65%
“…Indeed, in previous studies basal and post-dexamethasone cortisol levels were found to be higher in DAT patients than in age-matched healthy controls 3, 27100 Pavia, ltalia Accepted for publication December 27, 1989 I (10, 11). Moreover, plasma P-endorphin, whose secretion is directly controlled by CRF, is increased in DAT (12,13).…”
mentioning
confidence: 99%
“…The opioid peptides are involved in a variety of behavioral and physiological processes such as eating, drinking, reproduction, stress, pain, emotions, learning, and homeostasis (Morley et al, 1983;Ferin and Vande Wiele, 1984;Olson et al, 1990;Dondi et al, 1991;Laatikainen, 1991;Neumann et al, 1992;Russell et al, 1992), and opioid dysfunction has been implicated in several neurological/psychiatric disor- GPi HG IC IN INAH-1 INF IS LH LT LV MB MPA MT NA NBM oc third ventricle amygdala, central (Berger et al, 1981;Franceschi et al, 1986;Seizinger et al, 1986;Berger and Nemeroff, 1987;Cavagnini et al, 1987;Terenius et al, 1987;Franceschi et al, 1988;Chamberlain and Herman, 1990;Zis and Garland, 1991). A number of immunocytochemical and biochemical studies have shown that the peptides are concentrated heavily in the hypothalamus of various species, including humans (Bloch et al, 1978;Gramsch et al, 1979Gramsch et al, , 1982Kubek and Wilber, 1980;Maysinger et al, 1982;Pittius et al, 1983Pittius et al, , 1984Suda et al, 1985).…”
mentioning
confidence: 99%